2010
DOI: 10.1111/j.1365-2389.2009.01215.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling trace metal extractability and solubility in French forest soils by using soil properties

Abstract: Soil/solution partitioning of trace metals (TM: Cd, Co, Cr, Cu, Ni, Sb, Pb and Zn) has been investigated in six French forest sites that have been subjected to TM atmospheric inputs. Soil profiles have been sampled and analysed for major soil properties, and CaCl2‐extractable and total metal content. Metal concentrations (expressed on a molar basis) in soil (total), in CaCl2 extracts and soil solution collected monthly from fresh soil by centrifugation, were in the order: Cr > Zn > Ni > Cu > Pb > Co > Sb > Cd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 66 publications
(109 reference statements)
6
50
1
Order By: Relevance
“…See [17] for soil physicochemical properties and Pb concentrations and value of 6.0 for F. candida [12], which also increased Pb bioavailability for the collembolans. Therefore, the low pH may amplify the ecological risk caused by bioaccumulation of Pb in acid soils [26,29].…”
Section: Pb Uptake In the Collembolansmentioning
confidence: 99%
“…See [17] for soil physicochemical properties and Pb concentrations and value of 6.0 for F. candida [12], which also increased Pb bioavailability for the collembolans. Therefore, the low pH may amplify the ecological risk caused by bioaccumulation of Pb in acid soils [26,29].…”
Section: Pb Uptake In the Collembolansmentioning
confidence: 99%
“…Metal atmospheric pollution has already been studied for these sites through surface horizons of soils (Gandois et al, 2010a;Hernandez et al, 2003), bulk atmospheric deposition (Gandois et al, 2010b), and lichen bioaccumulation (Agnan et al, 2015). The metal concentrations registered in lichens collected on the trees considered for bioindication are given in Table 2.…”
Section: Study Areamentioning
confidence: 99%
“…Due to lower genotoxicity observed in the case of direct contact with soil, these authors concluded to a potential influence of soil organic matters. As soil solution represents the main available compartment for metals uptake by plants (Degryse et al, 2009;Gandois et al, 2010), one scientific question asked is the relation between aqueous extract of soil used in current genotoxicity to V. faba test and soil solution. Therefore, the objectives of the present study were to identify the correlation between Pb speciation, phytoavailability and genotoxicity to V. faba as a function of organic chelates nature and levels.…”
Section: Introductionmentioning
confidence: 99%